Exploring Novice EFL Teachers' Reflective Practice on Their Teaching Performances During Online Learning: A Narrative Inquiry Approach - Khoirina, Dini; Rochsantiningsih, Dewi; Setyaningsih, Endang (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The COVID-19 pandemic has caused sudden changes in the world of education, requiring teachers to adapt their teaching methods to online platforms. This narrative inquiry investigates the reflective practices of novice English as a Foreign Language (EFL) teachers in Indonesian schools during the transition to online learning. This research aims to explore how teachers reflect on their teaching performance and how this reflective practice influences their professional development. A qualitative approach was used to collect data from a sample of two novice EFL teachers working in schools in Indonesia. Data was collected through teachers' reflective journals that focused on their experiences and perceptions of online teaching practices. Teachers' reflections were analyzed thematically to identify common patterns and trends in their experiences. Preliminary findings suggest that novice EFL teachers actively engage in reflective practice to assess their teaching performance during online learning. Teachers demonstrated awareness of the strengths and weaknesses of their online teaching methods and expressed a willingness to experiment with new approaches to improve student learning. This study contributes to the understanding of how reflective practice influences novice EFL teachers' professional development in online learning contexts. This highlights the importance of ongoing self-evaluation and the potential benefits of incorporating reflective practice into teacher training programs. These findings have implications for policy makers, teacher educators, and school administrators, highlighting the need to support teachers in developing reflective skills to improve online teaching performance. Keywords: Reflective Practice, Novice EFL Teachers, Professional Development